2022
DOI: 10.3389/fneur.2022.781063
|View full text |Cite
|
Sign up to set email alerts
|

Monocarboxylate Transporter 1 May Benefit Cerebral Ischemia via Facilitating Lactate Transport From Glial Cells to Neurons

Abstract: Monocarboxylate transporter 1 (MCT1) is expressed in glial cells and some populations of neurons. MCT1 facilitates astrocytes or oligodendrocytes (OLs) in the energy supplement of neurons, which is crucial for maintaining the neuronal activity and axonal function. It is suggested that MCT1 upregulation in cerebral ischemia is protective to ischemia/reperfusion (I/R) injury. Otherwise, its underlying mechanism has not been clearly discussed. In this review, it provides a novel insight that MCT1 may protect brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…Among the 14 MCT isoforms (MCT1–14), MCT1, MCT2, and MCT4 are expressed in the brain and reportedly catalyze the proton-coupled transport of lactate ( Bergersen, 2015 ). Neurons express predominantly MCT2, which regulates lactate influx, whereas astrocytes express MCT1 and MCT4, which serve as lactate exporters during ischemia ( Zhang et al, 2022 ). In the current study, we speculated that PC may increase MCT1 and MCT4 in astrocytes in a P2X7 receptor-dependent manner to facilitate lactate release during severe ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 14 MCT isoforms (MCT1–14), MCT1, MCT2, and MCT4 are expressed in the brain and reportedly catalyze the proton-coupled transport of lactate ( Bergersen, 2015 ). Neurons express predominantly MCT2, which regulates lactate influx, whereas astrocytes express MCT1 and MCT4, which serve as lactate exporters during ischemia ( Zhang et al, 2022 ). In the current study, we speculated that PC may increase MCT1 and MCT4 in astrocytes in a P2X7 receptor-dependent manner to facilitate lactate release during severe ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been reported that lactate released into the extracellular space plays a key role as a modulator of multiple cellular processes via its transporters [monocarboxylate transporters (MCTs)] and receptor [hydroxycarboxylic acid receptor 1 (HCA1); Sun et al, 2017 ]. In cerebral ischemia, abundant lactate is produced by astrocytes, which store glycogen (a major source of lactate in ischemia); the astrocytes release the lactate into the extracellular space via MCT1 and MCT4 ( Zhang et al, 2022 ). Although several reports indicate that extracellular lactate is neuroprotective in cerebral ischemic injury ( Berthet et al, 2009 ; Horn and Klein, 2013 ), the role of lactate in brain ischemic tolerance remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term exposure to butyrate promotes MCT-1 expression via NF-κB while increasing the stability of MCT-1 gene regulation via microRNA [ 59 , 62 , 63 ]. Furthermore, MCT-1 supports oligodendrocyte survival [ 64 ], promotes lactate metabolism from oligodendrocyte to the axon, and encourages axonal plasticity [ 65 , 66 ]. MCT-2 is mainly expressed by neurons [ 67 ] and exclusively transports butyrate.…”
Section: Short-chain Fatty Acidsmentioning
confidence: 99%
“…MCT transporters are widely expressed in rat, mouse, or human brain endothelial cells, ependymocytes, and astrocytes, playing an important role in uptake into the brain [35]. MCTs facilitate lactate and monocarboxylates transport and cellular metabolism in a proton-dependent manner [36]. Apart from endogenous substances, MCTs also transport therapeutic drugs like atorvastatin and valproic acid [37].…”
Section: Localization Functions and Expression Of The Drug Uptake Tra...mentioning
confidence: 99%